Summer Hospitalization and Bronchial Asthma Make Treatment of Respiratory Syncytial Virus Infection Difficult: A Retrospective Study in Japan. (May 2022) - Oikawa, Kosuke; Ochiai, Hirotaka; Matsuhashi, Kazuhiko; Sakurai, Motoichiro; Suzuki, Manabu; Koganesawa, Masaya; Terada, Tomomasa; Ishii, Yoko; Kokaze, Akatsuki; Mizuno, Katsumi
In recent years, epidemics of respiratory syncytial virus (RSV) have been seen in the summer in Japan. Patients hospitalized in the summer used a high-flow oxygen administration device more frequently than patients hospitalized in the winter. This study was a retrospective study to examine the variables associated with duration of oxygen therapy and severe cases. Subjects were pediatric patients diagnosed with RSV infection and hospitalized for treatment during the 5 years from April 2014 to March 2019. Data from 292 patients were analyzed. Duration of oxygen therapy was significantly associated with bronchial asthma (partial regression coefficient: 0.897, P = .004). Hospitalization in summer was significantly associated with severe condition (adjusted odds ratio: 4.07, 95% confidence interval: 1.16-14.27). The present study showed that bronchial asthma is a risk factor for prolonged oxygen therapy and infection in summer is a risk factor for progression to severe condition in cases of RSV infection.